A Try To Relinquish The Hidden Felicity OF Law- Adeconstructive Reading OF Sylvia Plath’s Poem-Metaphors - A, Pranav; S, Arun (International Journal of Psychosocial Rehabilitation, 2020)
--“Metaphors For a Pregnant Woman” was the title that Sylvia Plath has given for her poem ‘Metaphors’, initially when it was written in her journal of 20th March 1959. The complete title clearly announcesthe stage of pragnancy and implications of motherhood. But sheherself shortened the title to “Metaphors” for publication which came a year later. This created the ambiguity in the poem. Plath wrote this poem mistakenly believing that she is pregnant. So shortening of the title opens a wide opportunity for interpretations. So this paper aims at expounding the poem “Metaphors” in a standpointthat it discusses and portrays the theme and symbols for childhood, applying the “Deconstruction Theory” of Jaques Derrida.